Microencapsulated PCM in the cement brick cavity: analysis of melting and solidification behaviour. Issue 1 (31st December 2022) - Mukram T, Anfas; Daniel, Joseph
ABSTRACT: The use of latent heat storage systems using phase change materials is becoming increasingly popular for passive building cooling applications. This paper introduces a novel cement brick design in which a microencapsulated PCM MEP29 is directly filled into the brick holes near the outer wall. The melting and solidification pattern of the PCM in the brick cavity is analysed numerically by shifting the location of the PCM holes from the outer to inner wall sides by 30, 40, 50, and 75 mm, respectively. Melting and solidification are both delayed when the PCM position is moved towards the centre of the brick. The melting time for mPCM 75 is 57 min longer than for mPCM 30 brick, with a 25-minute delay in the start of solidification. Furthermore, the unique brick design with offset PCM holes reduces the chance of heat reentry into the living space during solidification.